(untitled) (Journal of the College of Basic Education, 2026)
This research aims to explore the relationship between balance, simplicity, and modernity in print poster design, and how these principles interact to achieve high visual and communicative effectiveness. The study adopted a descriptive-analytical approach by analyzing a selection of design samples based on typographic design criteria such as composition, balance, visual rhythm, colors, typography, and symbolic meaning. The findings reveal that successful poster design is characterized by a thoughtful balance of visual elements while maintaining clarity and simplicity. The research also demonstrates that modern design principles—such as abstraction, clean lines, and flat colors—enhance the poster’s appeal when harmonized with balance. The study recommends the integration of these principles into academic design curricula and emphasizes the importance of training students in constructive visual thinking.